Reducing Congestion via Coordination of Signalized Intersection on Corridor KH. Abdul Halim Majalengka District - Yasa Kadek Satya Adi Dwi; Hardianto Dani; Sarjana Sri; Prasadda Ahmad Kemal (E3S Web of Conferences)
KH Abdul Halim Street have three intersections where the conditions are uncoordinated, resulting in vehicles that have just passed Mambo Market Intersection having to stop and wait for the green phase again at Abok Intersection, and a similar situation occurs at Tugu Kecap Intersection. Consequently, long queues, delays, and numerous stops, especially during peak hours, are unavoidable. Therefore, a thorough coordination analysis among the intersections is necessary to reduce traffic congestion at these three intersections. The purpose of this study is to analyze the signal coordination among the three intersections using Transyt 14.1 software. The research was conducted by analyzing primary and secondary data with Indonesian Highway Capacity Manual to obtain values for Capacity, Queue Length, Delay, Degree of Saturation, and Level of Service in the existing conditions, followed by analyzing the existing signal settings at these intersections using the Time-Distance Method diagram. The signal coordination analysis was carried out using Transyt 14.1, and the results from the software were compared with the existing conditions. The study results show that the delay has increased from the existing conditions at Pasar Mambo, Abok, and Tugu Kecap Intersections. The Degree of Saturation has decreased, and the Queue Length has also decreased. The novelty of this research lies in its practical application of signal optimization software to an understudied area, offering actionable recommendations for local governments to improve urban traffic flow and reduce congestion on busy corridors.